Veiling the Late Roman House. (May 2014) - Stephenson, John W.
Abstract : The period of late antiquity, c. ad 200–500, saw a dramatic increase in the social, political and religious significance of domestic textiles, as is revealed in references in literature and art, as well as in the finds of archaeological textiles in Roman Egypt. This paper explores the roles of textiles, particularly hangings and curtains, in such domestic settings in the late Roman period from a social perspective — how they served the increased concerns with privacy, visibility, mystery, boundaries and shifting gender relations that are amply attested in late Roman culture. I argue that, alongside more permanent forms of permeable boundaries, textiles were exploited for their unique inherent qualities in order to serve diverse needs in the late Roman house, and filled a central role in late Roman domestic life that was more far significant than their scant remains suggest today.